2023
DOI: 10.1088/1402-4896/acd81e
|View full text |Cite
|
Sign up to set email alerts
|

Influence of colored cross-correlated noise on stochastic resonance for an underdamped bistable system subjected to multiplicative and additive noises

Abstract: The stochastic resonance (SR) behavior for an underdamped bistable system with colored cross-correlated noise between multiplicative and additive noise is investigated. The stationary probability density is obtained under the condition of the detailed balance. The expressions for the signal-to-noise ratios (SNRs) for two initial states is deduced by applying two-state theory under the adiabatic condition. The analysis result indicates that the SR phenomenon takes place when the SNRs vary with the coupling stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…Adjusting the values of variables a and b can alter the shape of the potential function, which is crucial in determining whether the particles can successfully make a jump [11]. When comparing the potential function images of group A (a = 2, b = 0.5) and group B (a = 2.4, b = 0.5), it is evident that as the system parameter increases, the depth of the potential well deepens and the width of the potential well widens, making it more difficult for particles to make the jump.…”
Section: Potential Function Model For Bistable Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adjusting the values of variables a and b can alter the shape of the potential function, which is crucial in determining whether the particles can successfully make a jump [11]. When comparing the potential function images of group A (a = 2, b = 0.5) and group B (a = 2.4, b = 0.5), it is evident that as the system parameter increases, the depth of the potential well deepens and the width of the potential well widens, making it more difficult for particles to make the jump.…”
Section: Potential Function Model For Bistable Systemsmentioning
confidence: 99%
“…From Equation (11), it can be observed that the slope of the potential function curve contains cubic terms. This means that the slope of the curve will increase significantly as the displacement increases, as illustrated in Figure 5.…”
Section: Output Saturation Limitmentioning
confidence: 99%